PENGEMBANGAN MEDIA VIDEO ANIMASI KREATIF TOPIK TEKNOLOGI UNTUK KEHIDUPAN PADA SISWA KELAS V SDN SUKOSARI - Anisa, Nuril; Nuruddin, Muhammad (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
The development of animated video media as an effort to make the learning process more engaging through the optimal use of technology is an important step. This is because of the difficulty of students' understanding of the material if they only rely on conventional learning media such as teacher books and student books. By using creative animated video media, it is expected that the concepts in technology for life material can be conveyed more interestingly and easily understood by students. The development of this animated video media follows the Borg and Gall development model which has been simplified into 4 stages: introduction, development, product testing, and product dissemination. The selection of this model was modified to suit the needs of the research. The assessment of animated video media was carried out by media experts, material experts, educators, and fifth grade students of SDN Sukosari. The results showed that the media expert validators gave a score of 95% , categorized as highly valid and suitable for use, while the content expert validators gave a score of 80%, also categorized as highly valid and suitable for use. Additionally, the educators feedback was 80,2 % categorized as suitable for use without any revisions. Product trials were conducted involving 10 students, and the results showed of 89%, categorized as hghly engaging. Based on the overall data analysis. it can be concluded that the development of animated video media is feasible to use as learning media